Perceived Contributions of Translanguaging to Vocabulary Learning and Retention in an EFL Context - Fitria Aprilia; Neisya Neisya (English Language Education Department, Universitas Majalengka, 2026)
Abstract: Vocabulary learning remains a major challenge for learners of English as a foreign language, particularly in retaining newly learned words over time. While translanguaging has been widely recognized for enhancing comprehension, its role in vocabulary retention is still primarily understood from learners’ perspectives. This study investigates students’ perceptions of translanguaging in vocabulary learning and their perceived vocabulary retention in an EFL context. A descriptive quantitative survey design was employed, involving 30 students from an English Education Study Program. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using descriptive statistics, including percentage distributions and mean scores. The findings indicate that students hold highly positive perceptions of translanguaging in vocabulary learning (M = 4.26) and perceived vocabulary retention (M = 4.34). Students reported that translanguaging helps reduce perceived cognitive load, improves clarity, and helps them form stronger associations between English vocabulary and their first language, which they perceived as supporting memory and recall. The study concludes that translanguaging is perceived as an effective pedagogical strategy that potentially facilitates vocabulary learning and retention from the learners’ perspective.